2004
DOI: 10.2337/diabetes.53.suppl_3.s181
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Sensitive K+ Channel–Dependent Regulation of Glucagon Release and Electrical Activity by Glucose in Wild-Type and SUR1−/− Mouse α-Cells

Abstract: Patch-clamp recordings and glucagon release measurements were combined to determine the role of plasma membrane ATP-sensitive K ؉ channels (K ATP channels) in the control of glucagon secretion from mouse pancreatic ␣-cells. In wild-type mouse islets, glucose produced a concentration-dependent (half-maximal inhibitory concentration [IC 50 ] ‫؍‬ 2.5 mmol/l) reduction of glucagon release. Maximum inhibition (ϳ50%) was attained at glucose concentrations >5 mmol/l. The sulfonylureas tolbutamide (100 mol/l) and glib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
182
4
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(200 citation statements)
references
References 48 publications
12
182
4
2
Order By: Relevance
“…Activation of alpha cell voltage-gated Ca 2+ channels and the resultant glucagon secretion requires the activation of Na + channels. Several reports have shown that pharmacological blockade of Na + channels inhibits glucagon secretion [11,14,18,31]. Given that we had observed an augmentation of [Ca 2+ ] i associated with enhanced glucagon secretion upon inhibition of HCN channels, we hypothesised that Na + channels might mediate these effects.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Activation of alpha cell voltage-gated Ca 2+ channels and the resultant glucagon secretion requires the activation of Na + channels. Several reports have shown that pharmacological blockade of Na + channels inhibits glucagon secretion [11,14,18,31]. Given that we had observed an augmentation of [Ca 2+ ] i associated with enhanced glucagon secretion upon inhibition of HCN channels, we hypothesised that Na + channels might mediate these effects.…”
Section: Discussionmentioning
confidence: 83%
“…T-and N-type Ca 2+ channels and tetrodotoxin (TTX)-sensitive Na + channels are also important in the regulation of alpha cell electrical activity [11,[13][14][15][16][17]. One important feature of these alpha cell ion channels is their voltage-dependent inactivation when the cell membrane is depolarised [14,17,18]. Accordingly, a model for glucagon secretion has been proposed that highlights the important roles of ion channels in regulating glucagon secretion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of alpha cell Kv currents may then be expected to prolong or enhance action potential firing and glucagon secretion at low glucose concentrations. However, one study reports that the general Kv channel inhibitor 4-aminopyridine inhibited glucagon secretion [17]. Given the complex regulation of alpha cell function and previous observations that depolarisation of alpha cells may inhibit rather than stimulate alpha cell action potential firing and glucagon release [3,18], the role of the hyperpolarising Kv current in alpha cell function is far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that K þ ATP channels participate in the regulation of GCG secretion by glucose, since immunohistochemical and electrophysiological studies have detected K þ ATP channels in rat pancreatic alpha cells [7] and glucose and sulfonylurea effects on GCG secretion are deficient in SUR1 −/− mice [8]. Other studies, in the rat, suggest that only a minority of alpha cells have functional K þ ATP channels [9].…”
Section: Discussionmentioning
confidence: 99%